The Influence of Work Culture and Discipline on Employee Performance: The Intervening Role of Motivation at the Ministry of Tourism and Creative Economy - Atika Ayu Fitriayati; Suyanto; Sri Lestari Prasilowati (GoodWill, 2024)
Employee performance is vital for achieving organizational goals. At the Ministry of Tourism and Creative Economy, efforts to enhance performance include the use of the Personnel Management Information System (SIMPEG), fostering a positive work culture, and enforcing work discipline. Motivation plays a crucial mediating role in strengthening the relationship between these variables and employee performance. Despite ongoing initiatives, challenges persist, such as suboptimal SIMPEG utilization, inconsistent internalization of work culture, and uneven levels of discipline across the organization. This study adopts a quantitative approach using a survey method, with data collected via questionnaires distributed to randomly selected employees to ensure representativeness. Regression and path analysis were used to examine the direct and indirect effects of SIMPEG, work culture, and discipline on performance, with motivation as an intervening variable. The findings reveal that SIMPEG, work culture, and discipline significantly affect employee performance both directly and through motivation. SIMPEG enhances performance by improving transparency and access to information, which boosts motivation. A strong work culture and high discipline levels also positively influence both motivation and performance. Motivation emerges as a key mediating factor. Therefore, strengthening organizational culture, improving discipline, and optimizing SIMPEG usage are recommended to foster a productive and efficient work environment.